Gender responsive budgeting and its implementation efforts in Nepal - Bhul, Baburam (Journal of Management and Development Studies, 2022)
The purpose of this article is to analyze the contemporary experiences of gender responsive budgeting and its implementation efforts in Nepal. In recent years, the introduction of gender responsive budgeting has become an important topic on the government agenda to meaningfully internalize gender equality in public finance. Gender responsive budgeting, as an integral part in fiscal and budgetary decision making, can make gender equality and help differentiate the impacts on men and women. This article is based on the analytical and descriptive research design based on literature review of secondary data and information used for the analysis of the information. Therefore, the analysis of public expenditure and revenue policies and practices should consider this differentiated gender impact. Gender responsive budgeting in Nepal is committed to maintaining progressive social change, but efforts that are more concrete are needed to match political commitments. In the entire world, women only make 77 cents for every 1 earned by males. This gender responsive budgeting receives the highest share of the Nepal's budget in fiscal year 2021/22 (2078/79), accounting for 39 percent of all investments. Nepal has been associated with various gender responsive activities through different national policies, budgets, periodic and yearly plans and projects since the fiscal year 2007/08; and it is dedicated to the global commitment for the sustainable development goals and its timely achievements with the national targets; and leading the nation towards the gender inclusive society and gender friendly behaviors by the nation in all processes of the governance of Nepal.